Challenges and Opportunities of Ultrasound in Pregnancy at Primary Care in Low-Middle Income Countries - Dewi, Aulia Ulfah Mutiara; Kartasurya, Martha Irene; Purnami, Cahya Tri (Universitas Muhammadiyah Semarang, 2025)
The use of ultrasound in pregnancy was becoming more popular in LMICs as a routine antenatal care to detect early pregnancy complications. However, the challenges and opportunities of ultrasound in LMICs were not completely understood. This study aims to explore the challenges and opportunities of utilizing ultrasound in pregnancy at primary care in low-middle income countries. Method: The electronic databases from Springer, PubMed, and Science Direct through keywords “challenges AND opportunities AND ultrasound OR ultrasonography AND pregnancy OR pregnant AND primary care AND low middle income countries” were searched from 2014 to 2024 for studies available in English, qualitative or quantitative research, and free full text. A total of 8 articles from Australian rural/remote area, Kenya, Ethiopia, Rwanda, Vietnam, South Africa, and cross countries studies consist of Asia, Africa, and South America were included in this scoping review. Ultrasound training, availability of ultrasound equipment, and patient access to ultrasound service were the challenges of utilizing ultrasound. Stakeholder support and health systems became the opportunities to improve the utilizing and quality of ultrasound.Ultrasound examinations in LMICs still face several challenges. Opportunities that could overcome these obstacles would arise from the collaboration of multiple stakeholders.